Malthusianism Reexamined: A Qualitative Approach to Historical Perspectives - Nurul Izza, Nadia (SMART Insight, 2023)
The world's population projection will increase to 9.8 billion in 2050. The increase in population growth has made experts begin to focus and associated his research with Malthusianism. This study aims to identify and develop research related to the development of Malthusianism through indexed Dimensions with an approach using the NVivo 12 Plus software. The data were analyzed from 123 publications published in the last 123 years (1899-2022). This study also found that behavioral changes and technological innovations are now intricately connected with us in a global society so that problems such as food scarcity which according to Malthus was caused by an explosion that was not illuminated by the amount of food in the world, therefore, Allah SWT bestowed nature and its contents. to meet human needs. Every human being has a share or benefit of each, so there is no shortage in terms of food related to the increase in population that occurs. Even so, Malthus' theory reminds us that population growth must still pay attention to environmental sustainability, meaning that it must be adjusted to carrying capacity.